Logx+log(x+-21)=log(72)

Simple and best practice solution for Logx+log(x+-21)=log(72) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Logx+log(x+-21)=log(72) equation:


Simplifying
Logx + log(x + -21) = log(72)

Reorder the terms:
goxL + glo(-21 + x) = log(72)
goxL + (-21 * glo + x * glo) = log(72)
goxL + (-21glo + glox) = log(72)

Reorder the terms:
-21glo + glox + goxL = log(72)

Reorder the terms for easier multiplication:
-21glo + glox + goxL = 72glo

Solving
-21glo + glox + goxL = 72glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-72glo' to each side of the equation.
-21glo + glox + -72glo + goxL = 72glo + -72glo

Reorder the terms:
-21glo + -72glo + glox + goxL = 72glo + -72glo

Combine like terms: -21glo + -72glo = -93glo
-93glo + glox + goxL = 72glo + -72glo

Combine like terms: 72glo + -72glo = 0
-93glo + glox + goxL = 0

Factor out the Greatest Common Factor (GCF), 'go'.
go(-93l + lx + xL) = 0

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing g to the left, all other terms to the right. Simplifying go = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-93l + lx + xL)' equal to zero and attempt to solve: Simplifying -93l + lx + xL = 0 Solving -93l + lx + xL = 0 Move all terms containing g to the left, all other terms to the right. Add '93l' to each side of the equation. -93l + lx + 93l + xL = 0 + 93l Reorder the terms: -93l + 93l + lx + xL = 0 + 93l Combine like terms: -93l + 93l = 0 0 + lx + xL = 0 + 93l lx + xL = 0 + 93l Remove the zero: lx + xL = 93l Add '-1lx' to each side of the equation. lx + -1lx + xL = 93l + -1lx Combine like terms: lx + -1lx = 0 0 + xL = 93l + -1lx xL = 93l + -1lx Add '-1xL' to each side of the equation. xL + -1xL = 93l + -1lx + -1xL Combine like terms: xL + -1xL = 0 0 = 93l + -1lx + -1xL Simplifying 0 = 93l + -1lx + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 2(17.4)-6.4= | | 16-5y=6 | | 6x+24+2x+69=180 | | -2x+(-4)+(-12)+6x=0.16666666 | | 5=8=x/3 | | f(x)=x^3+3x^2-7x-21 | | (10+10)x=6000 | | y+11=2y-6.4 | | 8(1+5h)= | | x/-11=-10 | | 6a-2=2a+2 | | 3x+112+7x+40=180 | | 4e-2(2e+5)=-10 | | 2.3=z-4.8 | | 0=16t^2-200 | | m*-3.2=15 | | 7-5h=72 | | c=c+4b+4a | | -7g+5=-6g | | 6x-6+8-2x=2+2x | | 4q=8+2q | | 4y+2x-4y+7x= | | -0.14+4.75y-2.93-3.82y= | | 3x^3+4x=40 | | 8(2x+3)=53 | | 0.25r=0.6s | | 101x+4= | | 3x^3+4x-40=0 | | (x-3)+(3x+2)=4 | | 7x-3=5x+6-3 | | 41.2x+49.8-26.1x-30.1= | | T/0.3=1.7/0.9 |

Equations solver categories